A Comparative Evaluation of Different Impression Techniques for Post- Space: An In Vitro Study - Tandukar, Anjali; Guragain, Manjeev; Lohani, Junu; Tandan, Amrit (Journal of Nepalese Prosthodontic Society, 2025)
Introduction: For indirect technique of cast post and core, impression of post space is critical for the success of post core system. One of the main problems encountered while making impression of post space is incompleteness of impression and incorporation of voids leading to inaccurate post. Thus the present in vitro study is to compare 5 different impression techniques of post space so as to determine the technique that produces more accurate impression by assessing completeness of impression and number of voids in post space impressions.Methods: Five maxillary central incisors were endodontically treated and prepared for post and core. Post space impressions using polyvinylsiloxane were made using five different techniques i.e Technique I using 23 gauge anesthetic needle which acted as a vent placed till the base of postspace during injection of light body polyvinylsiloxane impression material followed by removal of the needle and placement of orthodontic wire to the depth of preparation as support; technique II using vent only; technique III using wire only; technique IV using no vent and no wire; Technique V using lentulo spiral and wire support. The samples thus obtained were evaluated for number of voids and completeness of impression under stereo microscope.Result: The completeness of impressions made by each technique was in the following order: Technique I>Technique II>Technique III and Technique V>Technique IV. Technique I was statistically significant than Technique III, IV and V. The total number of voids in each technique were maximum in the following order: Technique I